Designing successful professional meetings and conferences in education : planning, implementation, and evaluation - Mundry, Susan; National Institute for Science Education (U.S.) (Thousand Oaks, Calif. : Corwin Press, 2000)
1. Forums (Discussion and debate)--Handbooks, manuals, etc. 2. Education--Congresses--Handbooks, manuals, etc. 3. National Institute for Science Education (U.S.)
Faculty
Keywords: Forums (Discussion and debate) -- Handbooks, manuals, etc; Education -- Congresses -- Handbooks, manuals, etc